The Annexation of The General Judiciary Against Consumer Dispute Resolution Agency - Otih Handayani; Agus Riwanto; Panti Rahayu (Yuridika, 2021)
This article aims to analyze the authority of the Consumer Dispute Resolution Agency (BPSK) as Quasi-Judicial in handling consumer disputes as mandated in Article 49 paragraph (1) of Law No. 8 of 1999. This research is a normative legal study that is prescriptive and technical/applied. The research approach uses the Act approach. This legal research material uses primary legal materials and secondary legal materials. The technique of collecting legal materials through library research is then analyzed using qualitative methods. Supervision of the default clause stipulated in the credit agreement is the authority of BPSK; since 2013, the Supreme Court has consistently dismissed consumer disputes for credit agreements positioned as ordinary agreements, stating the parties to the dispute should take their case to the general Judiciary, as well as correcting BPSK's authority. This not only does not imply the principle of lex specialis derogate lex religious but also does not implement efficiency theory that ultimately harms consumers.